Diagnostics of structural integrity violations of avionics during impact tests - S. U. Uvaysov; A. V. Dolmatov; The H. Vo; Ngoc T. Luu; Cong D. Nguyen (Российский технологический журнал)
Objectives. With the continuous development of modern radio equipment in the field of aviation and space instrumentation, the requirements for accuracy, stability, and reliability of electronic equipment operated on spacecraft are also on the increase. Spacecraft avionic units (SAU) operate under special conditions and malfunctions, as a rule, are impossible to repair. SAU are hermetically sealed structures, making it difficult to assess their technical condition. The aim of this study is to increase the efficiency and reliability of detecting latent defects in SAU using the diagnostic method involving exposure to mechanical shocks.Methods. Based on known methods, a new diagnostic method is proposed which simulates mechanical processes under shock effects at the design stage. The aim is to evaluate the presence of various latent defects in SAU. In a serviceable state, the amplitude-frequency characteristics (frequency response) of SAU differ from the frequency response of SAU with defects which affect mechanical characteristics. It was for this reason that the diagnostic model of evaluating the technical condition of SAU without removal of devices was developed.Results. This work simulates the mechanical processes in SAU in a serviceable state in the presence of a variety of defect. It also involves experimental studies of mechanical characteristics in both serviceable and faulty states. After measuring the mechanical characteristics under the impact of shock loads, the data obtained is compared with simulation results in the presence of various defects. The comparison result is a report on the technical condition of SAU.Conclusions. The method of diagnosing SAU under mechanical shock impact enhances the efficiency of diagnosing latent defects during the production and operation of SAU.